Profile of Hypertensive Retinopathy in a Tertiary Centre in Western Nepal - Pun, CB; Tuladhar, S (Journal of Gandaki Medical College-Nepal, 2019)
Objective: The present study was done to find out prevalence of hypertensive retinopathy among patients attending in OPD in GMC. Methods: A hospital based cross-sectional study was performed among 200 hypertensive patients visiting eye OPD from Dec 2016 to Dec 2017. Detailed eye examination including fundus evaluation under mydriasis was done on all subjects and hypertensive retinopathy was graded according to Keith, Wagner and Barker classification by ophthalmologist using 90 dioptre lens. Patient having diabetes and other retinal diseases were excluded from the study. Data analysis was done using spss software. Results: The mean age of the patients was 60.58 ±12.26 standard deviation. In our study 56.5% patients had hypertensive retinopathy. Of which 31% had grade I, 19% had grade II, 6% had grade III and 0.5% had grade IV hypertensive retinopathy. The ratio of hypertensive retinopathy among male and female was 1.7:1. Conclusion: Hypertensive retinopathy is common among hypertensives and males are more prone to retinopathy than females.